Evaluation of Neutrophil-Lymphocyte Ratio, Platelet-Lymphocyte Ratio and Red Blood Cell Distribution Width-Platelet Ratio for Diagnosis of Premature Ovarian Insufficiency - Gülşah Ilhan; Fatma Ferda Verit Atmaca; Esra Altan; Ali Galip Zebitay; Hamdullah Sozen; Hurkan Akyol; Meryem Kurek Eken (Tehran University of Medical Sciences, 2017)
Objective: To evaluate whether systemic inflammatory markers (neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and red blood cell distribution width (RDW) to platelet ratio (RPR)) can be used as reliable markers for the diagnosis of premature ovarian insufficiency (POI) and to determine if there is a relationship between these markers and follicle stimulating hormone (FSH), Anti-Müllerian Hormone (AMH) levels. Materials and methods: Written and electronic medical records were reviewed using searches for diagnoses with the terms of 'premature ovarian failure', 'premature ovarian insufficiency'. Patients younger than the age of 40 were diagnosed to have premature ovarian insufficiency based on their menstrual history and sonographic examination and they were compared with healthy females. Complete blood counts, day-3 hormone profiles, AMH levels of all subjects were analyzed. Results: NLR was statistically higher in POI group compared with controls (p < 0.05). NLR had a positive correlation between FSH (r = 0.23, p = 0.045) and a negative association with AMH (r = - 0.27, p = 0.018). The area under ROC curve for NLR in POI was 0.66, with a threshold value 1.5 and sensitivity = 75.7 % and specificity = 46.0 %. Conclusion: NLR can be a marker for the diagnosis of POI. There is a close relationship between NLR and ovarian reserve markers such as FSH and AMH.